Lactobacillus reuteri DSM 17938 Probiotics May Increase CC-Chemokine Receptor 7 Expression in Infants Treated With for Colic - Savino, Francesco; Galliano, Ilaria; Savino, Andrea; Daprà, Valentina; Montanari, Paola; Calvi, Cristina; Bergallo, Massimiliano (Frontiers in Pediatrics, 2019)
Aim Studies have shown at Lactobacilli reuteri probiotics can affect cells that play a key role in the immune system. This in vivo Italian study investigated how Lactobacillus reuteri DSM 17938 influenced CC‑chemokine receptor 7 (CCR7) and interleukin 10 (IL-10) in breastfed colicky infants. Methods: Our University hospital in Turin recruited 50 healthy outpatients, at a median age of approximately one month, from September 2017 to August 2018. They were randomised to daily Lactobacillus reuteri DSM17938 (1×108 cfu) or a placebo for 28 days from recruitment. We collected peripheral blood and evaluated the expression of CCR7 messenger ribonucleic acid using the real-time TaqMan reverse transcription polymerase chain reaction method at baseline and after the study period. Results We found increased expression of CC‑chemokine receptor 7 in infants treated with the probiotic, but not the controls (p < 0.0026). No differences were observed for interleukin 10 after the study period in either group. Conclusion The increase in CC‑chemokine receptor 7 might have been a response to probiotic treatment. As a relatively small sample was used to conduct this study, our research needs to be replicated in different settings, and over time, to produce comparable findings.